2012
DOI: 10.1155/2012/530305
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Damage in Multiple Sclerosis Disease Subtypes Measured by High-Resolution Optical Coherence Tomography

Abstract: Background. Optical coherence tomography (OCT) has facilitated characterisation of retinal alterations in MS patients. Only scarce and in part conflicting data exists on different MS subtypes. Objective. To analyse patterns of retinal changes in different subtypes of MS with latest spectral-domain technology. Methods. In a three-centre cross-sectional study 414 MS patients and 94 healthy controls underwent spectral-domain OCT examination. Results. Eyes of MS patients without a previous optic neuritis showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
107
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 53 publications
16
107
0
6
Order By: Relevance
“…Reduced RNFL thickness in the absence of ON suggests possible subclinical episodes of ON or chronic axonal loss separate from acute attacks as a result of retrograde transsynaptic degeneration of retinal ganglion cells and their axons [18,19]. We also confirmed the results of previous studies that indicate a tendency of RNFL atrophy to be greater in ON-affected eyes than in unaffected eyes [20,21,22]. Previous studies reported that RNFL thickness was correlated with functional and structural measures of MS such as visual acuity, visual field, low-contrast letter acuity, contrast sensitivity, color vision, visual evoked potentials, brain atrophy assessed by magnetic resonance imaging and even quality of life [16,23,24,25,26].…”
Section: Discussionsupporting
confidence: 88%
“…Reduced RNFL thickness in the absence of ON suggests possible subclinical episodes of ON or chronic axonal loss separate from acute attacks as a result of retrograde transsynaptic degeneration of retinal ganglion cells and their axons [18,19]. We also confirmed the results of previous studies that indicate a tendency of RNFL atrophy to be greater in ON-affected eyes than in unaffected eyes [20,21,22]. Previous studies reported that RNFL thickness was correlated with functional and structural measures of MS such as visual acuity, visual field, low-contrast letter acuity, contrast sensitivity, color vision, visual evoked potentials, brain atrophy assessed by magnetic resonance imaging and even quality of life [16,23,24,25,26].…”
Section: Discussionsupporting
confidence: 88%
“…Studies using spectral-domain OCT have so far revealed that the retina in eyes without previous optic neuritis (non-ON eyes) shows thinner pRNFL and retinal ganglion cell layer thickness in most of the patients compared to healthy controls, and this was observed in all MS phenotypes including benign MS [4][5][6] . All of these OCT parameters have been associated with MS disability 7,8 and brain atrophy 7,9 and for this reason its application offers the promise of being used as an imaging surrogate of the MS disease course.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, retinal nerve fibre layer (RNFL) thinning detectable by optical coherence tomography (OCT) [14][15][16], delayed visually evoked potentials (VEP) [17], and visual dysfunction [16,18] also in MS patients without a history of ON may indicate subclinical damage to the visual system.…”
Section: Introductionmentioning
confidence: 99%